Advanced Design and Manufacture of Mechanoactive Materials Inspired by Skin, Bones, and Skin-on-Bones - Knothe Tate, Melissa Louise (Frontiers in Bioengineering and Biotechnology, 2020)
Life is mechanobiological. Natural living materials exhibit remarkable, emergent and smart properties under mechanical loading. Such materials are classified as mechanoactive, in contrast to electroactive polymers and materials that exhibit advanced properties when subjected to electrical stimulation. Cutting edge, multiscale imaging technologies have proven enabling for the elucidation of molecular to meso-scale structure and function of natural mechanoactive materials. Using Microscopy-Aided Design And ManufacturE, (MADAME) this perspective article describes mechanoactive properties of natural materials including skin-on-bones (periosteum) and bone itself. In so doing, it demonstrates the principle to emulate natural smart properties using recursive logic, the basis of many computer algorithms, and to design and manufacture mechanoactive materials and products using advanced manufacturing methods. In sum, the MADAME approach translates physically the computer science paradigm of recursion by implementing Jacquard textile methods, which themselves formed a historical basis for computing machines, together with additive manufacturing methods including multidimensional printing, stereolithography, laser sintering, etc. These integrated methods provide a foundation and translational pathway for scaled-up manufacture of disruptive mechanoactive materials that will find use in fields as varied as medicine, safety, transport and sports, for internal (implants) and external (wearables) applications.